Children with impairments learning numbers - Ahlberg, Ann (NOMAD Nordic Studies in Mathematics Education, 2006)
This research investigates children’s understanding of numbers when solving addition and subtraction word problems. A comparative approach – studying children who are blind, children with a hearing impairment and children without these impairments aims at illuminating and describing the differences and similarities between the three different groups. Thereby, the investigation contributes to the understanding of critical aspects characterising development of numerical competence in each of the three groups. The design of the study also makes it possible to describe children’s development of number concepts in the context of solving addition and subtraction word problems on a more general level.